Arazi deneyleri ile geoteknik tasarım - Nazilli, Hasan Bozkurt (Fen Bilimleri Enstitüsü, 1997)
Bu çalışmada arazi deneylerinden Standart Penetrasyon Deneyi (SPT), Koni Penetrasyon Deneyi (CPT) ve Menard Presyometre Deneyi (MPT) incelenmiştir. SPT, CPT ve MPT deneyleri hakkında genel bilgiler verildikten sonra bu deneyler ile ilgili literatürde yer alan kendi aralarındaki korelasyonlar ya da laboratuvar deney sonuçlarıyla korelasyonları ele alınmıştır. İzmit Alışveriş Merkezi geoteknik tasarımında SPT ve CPT verileri ile ayrı ayrı kazık taşıma kapasitesi hesabı yapılarak sonuçları değerlendirilmiştir. Çarşamba Havaalanı hizmet binalarının geoteknik tasarımında SPT ve MPT verileri ile ayrı ayrı temel taşıma kapasiteleri ve oturma analizleri hesaplanarak sonuçlar değerlendirilmiştir. SPT ve MPT ile ilgili mevcut korelasyonlar İstanbul Hafif Metro Projesi geoteknik inceleme sonuçları üzerinde irdelenmiştir.

The dependability and economy of foundation design depend on the correctness of the results which are obtained from soil researches the purpose of these researches is to provide parameters for solving soil problems in application. To obtained the most dependable parameters is the necessity of today ' s quality concept in civil engineering. The geotechnic parameters of sand, silt, clay and gravel should be given great importance to represent the foundation soil as close to the reality as possible by doing in-situ tests or laboratory test directly or making a careful and detailed research program. The purpose of soil research being made on land is to provide appropriate parameter which are used in calculating the load on structure of retaining or in determining the behavior of the soil under the loads of structures. The researches made on soil provide the possibility for engineers to evaluate the soils in various regions in making their designs. The correlation between various soil parameter themselves or between the parameter obtaind on land and the parameters obtained in laboratories are also very important in engineering projects. Some soil tests that are extensively used in determining the soil parameters which are vital in engineering are " THE STANDART PENETRATION TEST (SPT) ", " CONE PENETRATION TEST (CPT) and " MENARD PRESSIOMETER TEST (MPT) " which is being spreaded widely. It is very difficult to obtain undisturbed test sample from the soil and to create soil stresses in laboratories is very difficult, it is even impossible for some kind soils therefore the soil test in-situ are getting to become more importance in foundation projects. Standart Penetration Test (SPT) is a dynamic penetration test made on soil. The main principal of this test which is extensively used in the world is to determine the packing decree of the soil by reading the resistance that the soil layers show against the penetrometer and to have and idea about the resistance of soil. XI In geotechnic research of foundation soil ; SPT test is being done on the base of boring region to avoid the friction resistance and to gather information about the engineering parameters of the soil. On the other hand some indexes of soil are provided by testing disturbed samples which are taken by spoon sampler. SPT test is essentially simply to drive a standart spoon sampler into the soil. The spoon sampler ' s diameter is 2 " (50,8 mm), its inner diameter is 1 3/8 " (34,8 mm) and its length is 2 ' 8 " (813 mm). Driving it into soil is made by dropping the weight which is 140 lb (635 N) from a height of 30 " (760 mm). The standart tip is lowered to the test level after the base of the pit to be bored is cleaned. The spoon sampler is driven into the soil about 15 cm by dropping the weight from a lesser heights. By doing so the disturbed layer is passed and test is started with a clean soil layer. Then standart tip is driven into soil 30 cm more, the necessary number of drops of the weight for penetration of the tip for 30 cm is taken as standart penetration value or " SPT Resistance " and its shown as " N ". Number N is the total value for driving it in soil twice. In addition three times the first 15 cm drive are given a seperate value and they are compared. Cone Penetration Test (CPT) is a static penetration (bore by pushing) test on the soil. Especially by using Dutch Cone, the variation in shear resistance of soil by depth can be studied. Dutch borer, cone of go, tip cross-section as being 1 0 cm2 is thrust into the soil with a speed of 15-20 mm per second and the resistance at the tip is recorded. Resistance to cone, peripheral friction and total resistance are measured by different methods. First methods First cone and protective pipes are lowered to the test level, then the bars and cone are pushed to a depth of 70 - 80 mm with a constant speed and resistance at the cone is measured. International Soil Mechanics and Foundation Engineering Assosiation, European Static and Dynamic Penetration Test Method Commitee recommend the penetration speed and depth should be limited with the values of 1,25 m / min. and 7,5 cm. Later, either the cone or the bar is stopped and only the protective pipe is pushed down 200 mm and the perimeter friction is measured or the cone, bars and protective pipes are altogether pushed down and the total resistance is measured. In this method; if you substract the tip resistance from the total resistance you will get the resistance of the bars and the protective pipes namely you get the perimeter resistance. The same operation is repeated at every 200 mm and reading are registered. Xll Second method The cone, bars and protective piper all are pushed to the depth at which the measurements are to be done. Begemann (1965) developped a special cone and the perimeter resistance can be measured by using the cone and seperate cover which is about 250 mm above the cone and moving together with the cone and free from the protective pipe. After the cone is pushed about 40 mm, the cone, the friction sleeve pushed together along the rest, so the cone resistance and total resistance or total friction resistances are obtained seperately, but at the same time. CPT test equipment is made of pushing thrusting machine, reaction rig, a device registering the measurements and a standart cnical tip. Thrusting equipments are three types which are light, medium and heavy rigs. Light rigs are mainly with a capacity of 20-25 Kn and used for examining the weak layers of soil. The penetrometer that is being used is mechanical and jacketed cone. In case of the light rigs is used for medium packed sands or hard clays their penetration depth is limited. The main principal of the Menard Pressuremeter Test (MPT) is to measure the relation between soil deformation and pressure by widening the cylindrical hole in the soil. In practice, those measurement are made by openinig a hole down to the level at which the test is to be done. The probe of pressuremeter is inserted in the soil to widen the hole, it is blown and the changes in the volume of the hole is recorded.The probe is designed in such ways that the length of the hole stays constant and the expansion of volume is in radial direction. The lateral pressure probe was introduced first by Kogler in 1930 and this test method has been improved by L. Menard, a French investigator, in 1950, with the name of pressuremeter. E pressuremeter It is the first developped pressuremeter. It was started to be used in 1958, but this type of pressuremeter has not been produced for a long time, however it is still used in some bride and highway laboratories. The pressures up to 2000 or 2500 Kpa can be applied with this type pressuremeter. GC pressuremeter Today, it is the most popular type of pressuremeter. Normally it can be reached to a pressure of 2500 Kpa. However it is possible to reach to a XUl pressure of 4000 Kpa with some changes. The water volume in control chamber is900 cm3. It is not composed of three seperate parts like the other pressuremeters instead it has a single measuring cells at both ends of measuring chamber. The shapes and lengths of the protective cells do not change unless the length of measuring cell changes.For stabilizing this during the expansion of probe, the water pressure in measuring cell is kept higher than the gas pressure in protective cells. GB pressuremeter GB pressuremeter is equipped to reach a pressure of 10000 Kpa. Each of the three units of the probe is free from the others and each is blown with water. The measuring cell is fed from a container with a capacity of 800 cm3, on the other hand the protective cells are fed from another container with the same capacity. Pressuremeter is composed of three parts which are borer, control unit and pipe set. The water is used to measure the volumetric changes in the circular hole in the soil. The water is kept in an elastic, tight rubber chamber which is called " measuring chamber ". The measuring chamber is supported by rubber cells at the top and bottom to allow the horizontal expansion of the chamber; but not the vertical expansion so it help the hole to be widened enough. Those cells are called " protective cells " which are filled with a gas and they are kept at the same pressure with e measuring chamber ". Those protective cells prevent the measuring chamber wall from expanding upward or downward in the hole. Since, the rubber wall is elastic enough it applies a uniform pressure on the perimeter of hole during the test, the normal conditions are created in the soil around the hole. The steel bar that is connecting the three cells which make the pressuremeter borer makes them work smoothly besides that provides connection with pipe set coming from control unit. The control unit is placed somewhere on the soil close to the hole. Its function is to control and operate the expansion of probe. It does that by applying a certain pressure on the probe according to coming information and by measuring the changes in volume. The source of pressure is a pressurized glass bottle. The water to be sent to measuring chamber is measured in a cylinderical glass tube on which volumetric scale is marked. This tube is called " volumeter ". The valves and fittings in the control unit provide to drop the pressure in the gas bottle according to the need, to connect the pipe set which go to the borer, to refill " volumeter " and to empty the air from the borer and drop the pressure to none. Pipe set provide circulation of water and gas between control unit and probe. XIV The common features of pressuremeters are given below ;. Every probe has three cells those are central measuring cell and two protective cells.. According to the test principal, any deformation in measuring cell is accepted to be caused by the deformation of soil.. Because of its incompressibility and simplicity in usage the water is used in measuring the deformation of the the measuring cell.. The energy that deforms the probe is provided from pressurized gas bottle.. The probe diameter is defined by the " Diamond Core Drill Manufecturer ' s Association " (DCDMA) standarts. There are two main reasons for production various pressuremeter by Menard Trainning Center ; 1. Matching the types and conditions of soils to be examined. ( The first series of production were designed to test different type of soil.from soft soil to mixed soils. Nowadays those tests are being applied to every kind of soil including rocks ) 2. The correction of technical problem in previous series of production. SPT Test give very good results when it is done on clean fine and medium grain size sands, very fine sand with gravel and sand with little silt. We can get information about tip resistance and perimeter friction of friction piles by doing this test. The consistency of clay, shear resistance and compressibility can be examined by studying the relation between " Standart Penetration Resistance (N) " and the shear resistance of the undrained soil that can be obtained by doing tests. As it is true for other soil test, some application errors in SPT test may cause somewhat different evaluations. CPT Test is static penetration test which is oftenly used in U.S.A. and Europe. The tip resistance and perimeter friction are measured in this test which is used widely in projecting piles. CPT test is an ideal test for soil layers which contain soft clay and sand. MPT Test is used in defining the behaviours of foundation without any need of supplementary test results. To be applicable on various types of soils is one of the main advantages. In addition to this it is applicable in situations where good quality and high level representative samples are not possible to be taken which are very much needed in laboratory tests. XV Pressuremeter cannot measure Mohr, Coulomb Resistance Parameters directly as it is done in laboratory tests.When it is looked at carefully, it will be seen that the results of SPT and MPT are mostly completing each other. By this study, SPT - CPT - MPT tests are introduced, general information and correlations between them are summarized. In the Project Of İzmit Shopping Center ; the calculations of bearing capacity of the pile were done by using the results SPT and CPT in-situ tests and the test that were made in laboratory. Also in The Projects Of Services Buildings Of " Çarşamba Airport " in Samsun, the bearing capacities of foundations and the analysis of settlements ; are calculated by using SPT and MPT test results and made in laboratory.
The Geotechnic design with in situ tests
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1997
Keywords: Geometrik tasarım; Konik penetrasyon testi; Menard presyometre deneyi; Standart penetrasyon testi; Standart peneration test; Conic penetration test; Geometric design; Menard presyometer experiment